Migraine Disorders - Prevalence and Disability Evaluation along with its Association with Sleep Quality among Undergraduate Medical Students - Dr. Sai Lavanya Patnala; Anu Mohandas; Baby Shalini Muppalla; Pavani Varma; Snigdha Pattnaik; Suditi Sharma; Hamsa Priya Bhuchakra (Bengal Journal of Otolaryngology and Head Neck Surgery, 2025)
Introduction: Headache is a prevalent issue among medical students, stemming from academic pressures, clinical responsibilities, and emotional stressors, with implications for reduced academic performance and co-morbid psychiatric illnesses. Of particular concern is migraine, which may disrupt the acquisition of patient care skills. This study aimed to assess the prevalence of migraine, its associated disability, and contributing factors